Improving the monacolin K to citrinin production ratio in red yeast rice by an X-ray-induced mutant strain of Monascus purpureus - Apinun Kanpiengjai (2018)
© 2018, Institute of Bioorganic Chemistry. All rights reserved. Red yeast rice (RYR), which is fermented by Monascus purpureus CMU002U, contains high amounts of monacolin K – a secondary metabolite with health benefits that has consequently gained interest in research. Although monacolin K is recognized as an anti-hypercholesterolemic agent, citrinin is a toxic substance that is simultaneously synthesized during RYR fermentation. An X-ray mutagenesis of M. purpureus CMU002U was conducted to achieve a lower-citrinin-producing strain with an improvement of monacolin K to citrinin (M/C) ratio. Among the selected mutants, CMU002UXX-32-44 was the strain having the most potential with regard to the lowest level of citrinin production capability, along with an improved M/C ratio (from 1460 to 1790 when compared with the parental strain). Furthermore, the medium and conditions for RYR fermentation using glutinous rice as the substrate were statistically optimized. The Plackett and Burman design revealed that moisture content and incubation time were the most significant factors enhancing monacolin K production, besides the addition of alternative mineral and nitrogen sources. After the application of a response surface methodology, the maximum monacolin K concentration of 6428 mg/kg was predicted and successfully produced with 90% validation when the moisture content and incubation time were set to 75% and 38 days, respectively – leading to a 5.1-fold increase in monacolin K. Under these conditions, RYR was contaminated with citrinin levels acceptable to the international standards for citrinin in food supplements, whereas the M/C ratio was improved to 3990. Therefore, this mutant displayed a strong potential for use at the industrial scale.